Pengaruh Pemberian Gula Semut dan Jahe terhadap Penurunan Mual Muntah Ibu Hamil Trimester I - Ati Mardiyati; Adriana Palimbo; Nita Hestiyana (Pusat Riset dan Inovasi Nasional, 2023)
Pharmacological treatments such as vitamin B6 can be used to treat nausea, vomiting. However, pregnant women can use natural remedies such as ant sugar to prevent drug side effects. The purpose of the study was to determine the effect of giving ant sugar and ginger on reducing nausea vomiting in pregnant women in the first trimester. This type of research uses pre post with control group design. The sample was 10 respondents of the intervention group and 10 respondents as a control group. Bivariate analysis is a statistical homogeinity test. The results of the study that the incidence of nausea vomiting in pregnant women trimester 1 before being given a combination therapy of ant sugar and ginger was obtained as many as 3 respondents (30%) mild category, 6 respondents (60%) medium category and 1 respondent (1%) weight category. After being given ant sugar and ginger, there was a decrease in vomiting to 3 respondents (30%) not nauseated vomiting, 3 respondents (30%) mild category, 3 respondents (30%) moderate category and 1 respondent (1%) weight category. The results of statistical tests using marginal homogeinity tests in this study showed a p value of 0.014 (< 0.05). The implication that giving ant sugar and ginger has an influence on reducing nausea vomiting in first trimester pregnant women.